The Effect of IT-Enabled Business Process Reengineering On Banks Performance (Al-Mansour Journal, 2022)
Until some 40 years ago, the process of bank management was based on assumptions and experience, and with the appearance of computers, management was increasingly based on empirical data and analytical processes. Computerization of banking has began with data processing, then it was moved on to information processing, so that the processing of specialized knowledge in the function of decision-making could be reached in the latest period. Information technology and informationsystems are increasingly being designed as expert systems, which are in function of banking experts,Due to accelerated expansion of electronic banking systems, it comes to major upheavals in the essence of ebanking, which is becoming synonymous with modern banking. Today, banking business is entirely based on technical and technological resources and ICT becomes a guide for strategy and reengineering.
Keywords: Bank Management; Data Processing; Decision-Making